Diagnosis of health-related physical fitness in office workers of the Federal University of Viçosa - Cristiano Diniz da Silva; José de Fátima Juvêncio (Universidade Federal de Santa Catarina, 2004)
The behavioral demands and the particularities of the activities performed by the employees from offices at the Federal University of Viçosa can offer a series of negative factors for health. The interface with the computer and task characteristics give a great body and also cognitive demands, that allied to several factors can represent the appearance or worsening repetitive lesions and/or work related problems in the skeletal muscle (Cumulative Trauma Disorders) . This study aimed to diagnose the workers' situation in relation to General Human Factors (GHF) and level of Health-Related Fitness (HRF)components: cardiorrespiratory; flexibility; strength and percent of body fat. The sample was composed by 46 workers. For both sexes, the GHF variables of higher significance were: "posture perception"; "sensation of local pains and those from some movement or task" in the back, shoulders and arms areas. Referring to HRF, both sexes presented unsatisfactory levels for trunk-hip flexibility " and great part of men were classified as" below average " in the push-up test" which are risk factors for CTD. Significant portion of them presented high percent of body fat (25,0%) or were "obese" (14,2%). In general terms of HFR, there should be interventions, such as physical activity and/or sports programs for this group of employees at this institution. It is suggested that actions should also be taken in the leisure activity offering, once it was shown that 39,2% of the men and 44,4% of the women have in TV their main leisure activity. RESUMO As exigências comportamentais e as particularidades das atividades desenvolvidas pelos funcionários de alguns setores caracterizados como escritórios da Universidade Federal de Viçosa podem estar potencializando uma série de fatores negativos para a saúde destes. A interface com o computador e a característica da tarefa levam a uma forte exigência física e também cognitiva, que aliadas a outros fatores poderá propiciar o surgimento e/ou agravamento de "lesões por esforço repetitivo" e/ou "distúrbios osteomusculares relacionados ao trabalho" (L.E.R./D.O.R.T). Este estudo buscou diagnosticar a situação destes trabalhadores com relação a Fatores Humanos Gerais (FHG) e o nível de Aptidão Física Relacionada à Saúde (AFRS) nos componentes: cardiorrespiratório; flexibilidade; força e percentual de gordura corporal. A amostra foi composta por 46 profissionais. Nos FHG, em ambos os sexos, as variáveis de maior significância foram: "percepção postural"; "sensação de dores localizadas e as de conseqüência de algum movimento ou tarefa" na região das costas, ombros e braços. Referindo-se a AFRS, ambos os sexos apresentaram níveis "insatisfatórios" para a saúde na "flexibilidade tronco-quadril" e uma grande parcela de homens classificou-se em "abaixo da média" no teste de "flexão/extensão de cotovelos", fatores predisponentes para L.E.R./D.O.R.T. Grande parcela deles ainda apresentou o percentual de gordura corporal como "elevada" (25,0%) ou mesmo "obeso" (14,2%). Em termos gerais da AFRS devem ser feitas intervenções, tais como programas de atividade física e/ou esportivas para esta classe de funcionários nesta instituição de ensino superior. Sugere-se ações nas atividades de lazer, onde foi constatado que 39,2% dos homens e 44,4% das mulheres tem na televisãosua principal atividade de lazer.